Not-intentional learning in the complexity of school environment: An emerging matter and actions’ facilitator towards peacebuilding - Becerra Martínez, James Frank; Cárdenas Forero, Oscar Leonardo; Moncada Rodríguez, María Anais; Negrete Soler, Edith Constanza; Prieto Acuña, Ángela; Uribe Garzón, Sonia Milena (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2017)
There are some interactions, some learning in the school environment that do not appear in relation with curriculum content, academic activities or teacher’s pedagogical intentions, but also involve types of languages, behaviors, attitudes and expressions that are not explicit in these activities, but they become visible in the convivial dynamics of the students. These particular ways of relating happen without the direct mediation of the school, becoming learnings that line of great importance in extent that it seems that they are the market of convivial relations, enhancers or inhibitors of the school learning’s and the actions to build peace at school.